Complete learning disabilities handbook : ready-to-use strategies & activities for teaching students with learning disabilities - Harwell, Joan M., 1936- 4 0 16; Jackson, Rebecca Williams; 5 (San Fransisco, California : Jossey-Bass, 2008)
Provides suggestions and materials for meeting the special needs of learning-disabled students, featuring tools for diagnosis and assessment, strategies for classroom management, solutions to common problems, guidelines for intervention, and techniques for helping older learning-disabled students.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Education;Education -- Learning disabilities;Remedial teaching;Learning disabled youth;Teaching;Handicapped children -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2